2015
DOI: 10.1186/s12889-015-1753-y
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster-associated mortality in Europe: a systematic review

Abstract: BackgroundReactivation of latent varicella zoster virus, partly due to age-related immunosenescence and immunosuppressive conditions, results in herpes zoster (HZ) and its associated complications. The management of the most important complication, post-herpetic neuralgia (PHN), is challenging, particularly in the elderly, and is generally unsatisfactory. No previous reviews have reported the incidence of HZ-associated mortality.MethodsWe carried out a systematic literature review to identify studies and datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 38 publications
4
39
0
3
Order By: Relevance
“…Thirdly, the event of interest must not censor the observation period—for example, if the zoster event increases the likelihood of death. This assumption is fulfilled, as zoster is rarely associated with increased mortality 35. Supplementary box e-1 provides a detailed discussion of these fundamental assumptions.…”
Section: Methodsmentioning
confidence: 98%
“…Thirdly, the event of interest must not censor the observation period—for example, if the zoster event increases the likelihood of death. This assumption is fulfilled, as zoster is rarely associated with increased mortality 35. Supplementary box e-1 provides a detailed discussion of these fundamental assumptions.…”
Section: Methodsmentioning
confidence: 98%
“…38,39 HZ fatality figures were calculated from Ultsch et al (2011), using the same approach as applied in a previous review; mortality rates reported per 100,000 person-years were calculated as the HZ case fatality rate. 10,40 Costs Direct medical and indirect costs related to HZ were taken from Ultsch et al (2013), who used a retrospective database combining both patient-related billing data from a SHI and patient-related treatment documentation from a regional Association of SHI-Accredited Physicians. Individuals of all ages with a HZ diagnosis in 2005-2008 were included and observed for two years (one HZ diagnosis-free year before diagnosis and one year after HZ diagnosis).…”
Section: Epidemiological Inputsmentioning
confidence: 99%
“…Herpes zoster, or shingles, is a neurocutaneous disease that occurs through reactivation of latent varicella zoster virus (the virus that causes chicken pox). 1 A quarter of the population is at risk of developing herpes zoster during their lifetime, 2 3 4 5 6 and two thirds of people with the disease are aged 50 years or older. 7 The morbidity from herpes zoster increases with age.…”
Section: Introductionmentioning
confidence: 99%